Assistance teaching work of the stomatology professionals in the confrontation to COVID-19 - Rafael Alberto Clavería Clark; Katiuska Rodríguez Guerrero; Michel Lescay Arias; María de los Ángeles Cuevas Gandaria; Susel Silva Guevara (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The COVID-19 is an infectious disease caused by the SARS-CoV-2 virus, that is why, specifically in the case of stomatology, the indispensable biosecurity measures should be taken to preserve the health of the medical personnel and patients.  Objective: To characterize the assistance teaching work of health professionals in Mártires del Moncada Provincial Teaching Stomatological Clinic from Santiago de Cuba during the COVID-19.  Methods: An observational, descriptive and cross-sectional study was carried out, with retrospective collection of the information between March, 2020 and September, 2021.   Results: In the teaching work, from a total of 75 pregraduate degree students promoted 41 in the state exam and 24 of postgraduate degree students; also 15 professors changed categories, either scientific or teaching. In the assistance work the urgencies visits prevailed in the three periods (62.5 %), followed by the specialized visits (28.5 %).   Conclusions: The assistance teaching work in the different stages of the epidemic was characterized to achieve the different promotions in the pregraduate degree and postgraduate degree studies, as well as for the care to patients with stomatological emergencies, fundamentally coming from other health areas, always with the demands and control on the fulfillment of the biosecurity measures plan.